Effect of Bearing Elastic Deformation on the Turbulent Thermohydrodynamic Lubrication of Misaligned Plain Journal Bearings - Abass, Basim Ajeel; Ghani, Sudad Nori (Nahrain University College of Engineering Journal, 2014)
This paper investigates the effect ofbearing shell elastic deformation on thesteady state behavior of misaligned journalbearings. Performance trends of elastic andrigid bearings with different degree ofmisalignment (Dm) have been compared.Bearing shell elastic deformation, thermaleffects, pressure and temperature variationfor a bearing working under turbulentlubrication have been taken intoconsideration. It is found that misalignedbearings working at higher misalignmentcoefficients have higher load carryingcapacity since the oil film thicknessapproaches to zero in this case. Consideringthe effect of bearing shell elastic deformationwith the effect of oil film temperature causeslower values of bearing load. Some of theresults obtained in this paper have beencompared with that published by otherworkers and found to be in a goodagreement.